2018
DOI: 10.3174/ajnr.a5702
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of MRI Biomarkers in the Substantia Nigra to Discriminate Idiopathic Parkinson Disease

Abstract: BACKGROUND AND PURPOSE:Several new MR imaging techniques have shown promising results in patients with Parkinson disease; however, the comparative diagnostic values of these measures at the individual level remain unclear. Our aim was to compare the diagnostic value of MR imaging biomarkers of substantia nigra damage for distinguishing patients with Parkinson disease from healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 36 publications
10
66
1
2
Order By: Relevance
“…Voxel‐wise volumetric analysis was carried out using SPM12 implemented in Matlab 2015a . Quantitative analysis of neuromelanin‐sensitive images was carried out using a previously validated method with good interrater and intrarater agreement . Diffusion data analysis was performed using FSL Diffusion Toolbox) (FMRIB Centre Software Library, Oxford University, UK).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Voxel‐wise volumetric analysis was carried out using SPM12 implemented in Matlab 2015a . Quantitative analysis of neuromelanin‐sensitive images was carried out using a previously validated method with good interrater and intrarater agreement . Diffusion data analysis was performed using FSL Diffusion Toolbox) (FMRIB Centre Software Library, Oxford University, UK).…”
Section: Methodsmentioning
confidence: 97%
“…9 Quantitative analysis of neuromelaninsensitive images was carried out using a previously validated method with good interrater and intrarater agreement. [10][11][12] Diffusion data analysis was performed using FSL Diffusion Toolbox) (FMRIB Centre Software Library, Oxford University, UK). Further details of the analysis can be found in Supplementary material.…”
Section: Genetic Analysismentioning
confidence: 99%
“…To evaluate the accuracy of segmentation for each setting, a second examiner performed the segmentations. For NM images, the contours of the SN were manually drawn around the area of high signal intensity as previously described . For 7T T2*‐w images, the SN was defined as the area of hypointensity ventral to the red nucleus and dorsal to the cerebral peduncle.…”
Section: Methodsmentioning
confidence: 99%
“…For NM images, the contours of the SN were manually drawn around the area of high signal intensity as previously described. 16 For 7T T2*-w images, the SN was defined as the area of hypointensity ventral to the red nucleus and dorsal to the cerebral peduncle. The STN was also manually segmented using 7T images.…”
Section: Regions Of Interestmentioning
confidence: 99%
“…In 1986, Duguid et al [17] observed a reduced width of SN pars compacta in patients with PD using a 1.5T scanner. Since then, several MR studies report a decrease in signal intensity [18][19][20][21][22][23][24][25][26][27][28] and volume or surface reduction [19,21,22,25,26,[28][29][30][31][32][33][34] of the SN in patients with PD. Moreover, discrimination between PD patients and other Parkinsonian syndromes also yields reliable results [29,35,36].…”
Section: Introductionmentioning
confidence: 99%